Dynamic Workload Adjustment in Condition-Based Maintenance: A Review of Robust Optimization Approaches for Production Systems - A. Sigit Pramono Hadi; Benardi Benardi; Cahyatih Kumandang (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores